2020
DOI: 10.1002/mp.14485
|View full text |Cite
|
Sign up to set email alerts
|

Acuros® dose verification of ultrasmall lung lesions with EBT‐XD film in a homogeneous and heterogeneous anthropomorphic phantom setup

Abstract: Purpose Modern type ‘c’ dose calculation algorithms like Acuros® can predict dose for lung tumors larger than approximately 4 cm3 with a relative uncertainty up to 5%. However, increasingly better tumor diagnostics are leading to the detection of very small early‐stage lung tumors that can be treated with stereotactic body radiotherapy (SBRT) for inoperable patients. This raises the question whether dose algorithms like Acuros® can still accurately predict dose within 5% for challenging conditions involving sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(89 reference statements)
2
2
0
Order By: Relevance
“…The main finding of the present study is that a workflow for palliative RT in bone metastases was feasible simulating a single clinic visit when a maximum 6-week old dCT is used for initial treatment planning, followed by on-couch plan adaptation based on a CBCT. Specifically, on-couch plan adaptation was able to account for changes in body contours and target volume, and this approach allowed for the use of highly conformal OAR sparing plans.As high gamma pass rates were observed for the adapted plans consistent with previous work, 27 we concluded that clinically acceptable treatment plans could be achieved without the use of a dedicated pCT. Approximately 75% of the patients required the adaptation of target contours by a radiation oncologist.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The main finding of the present study is that a workflow for palliative RT in bone metastases was feasible simulating a single clinic visit when a maximum 6-week old dCT is used for initial treatment planning, followed by on-couch plan adaptation based on a CBCT. Specifically, on-couch plan adaptation was able to account for changes in body contours and target volume, and this approach allowed for the use of highly conformal OAR sparing plans.As high gamma pass rates were observed for the adapted plans consistent with previous work, 27 we concluded that clinically acceptable treatment plans could be achieved without the use of a dedicated pCT. Approximately 75% of the patients required the adaptation of target contours by a radiation oncologist.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, on‐couch plan adaptation was able to account for changes in body contours and target volume, and this approach allowed for the use of highly conformal OAR sparing plans. As high gamma pass rates were observed for the adapted plans consistent with previous work, 27 we concluded that clinically acceptable treatment plans could be achieved without the use of a dedicated pCT.…”
Section: Discussionsupporting
confidence: 87%
“…41,42,46 Measurements in lung phantoms, particularly of small fields, are becoming increasingly important as more departments attempt to commission or validate treatment planning system calculations for stereotactic ablative radiotherapy treatments of small lung lesions. 21,26,27 Film measurements in lung phantoms should be corrected using values in Tables I--III, as shown in Eq. (1).…”
Section: Discussionmentioning
confidence: 99%
“…22 Lung tumor sizes being treated can be as small as 3 mm in diameter, 23 and advancing imaging techniques and motion management strategies are allowing margins to be reduced, sparing more healthy lung tissue. 24,25 It is therefore clear that accurate experimental dose verification of very small fields in lung phantoms is imperative (see, e.g., 26,27 ).…”
Section: Introductionmentioning
confidence: 99%